Systems safety in nonoperating room anesthesia locations. Issue 4 (5th August 2022) - Tobin, Catherine D.; Bridges, Kathryn H.
Abstract : Purpose of review: Nonoperating room anesthesia (NORA) care is an area of rapid growth over the last decade. However, literature describing safety systems in NORA is limited. This review evaluates historical safety models described by Donabedian and Reason, assesses the NORA environment and safety concerns that may contribute to adverse events, and provides potential solutions via a human-centered systems safety design. Recent findings: Systems Engineering Initiative for Patient Safety (SEIPS) 3.0 provides a framework for quality and patient safety improvement. Although the previous SEIPS 2.0 model has been used to evaluate NORA environments with focus on the case volume, high productivity pressure, and significant physical constraints common to NORA sites, literature describing SEIPS 3.0 in relation to NORA care is sparse. Given the rate of malpractice claims for death in NORA settings, solutions that address the multifactorial nature of adverse events are needed. Summary: The SEIPS 3.0 model may be applied to NORA care. Changes should focus on staffing ratios, staff/patient education, checklist utilization, burnout prevention, scheduling efficiency, anesthesia workstation standardization, communication improvements, room layout, medication and supply availability and storage, and the global managerial approach. Team members must demonstrate flexibility and a willingness to adapt to successfully implement change.